Die thorakolumbale Wirbelsäulenform männlicher Leistungsvolleyballspieler - Dalichau, S.; Scheele, K. (Deutsche Zeitschrift für Sportmedizin, 2002)
The aim of this study was to evaluate the influence of the motoric demands of competitive volleyball on the thoracolumbar spinal configuration. For that reason the spinal profile (C7S2) of 85 male active volleyball players aged 24.4 ± 4.9 years with a sporting exposure of 12.5 ±3.2 years and of 1347 age and gender-matched non- and recreational sportsmen was recorded by means of the non-invasive ultrasonic-controlled contact rod. Compared to the control group, the angle of kyphosis of the athletes was significantly increased in the sagittal projection. In the frontal and transversal plane the parameters side of the hitting arm and the player position of the attacker induced a fundamental uni-lateral extension of the pelvic and the shoulder-pelvic tilt as well as shoulder-pelvic rotation. In contrast passing and defending player positions showed a significantly tighter distribution of the data around the individual anatomic spinal zero position than the controls. Particularly the sports-specific skills like as hitting and serving in competitive volleyball seem to influence the spinal configuration in a special way. Although there is no provable connection between the spinal profile and the prevalence of sports injuries, the results of this study as well as the literature indicate the necessity of careful planning and carrying out of long-term and continuous training development for protecting spinal structures. For that, the individuality of the athlete and regular sports medical controls should be taken into special account.